Converting tacit knowledge into explicit knowledge in organisations - M.M. Hugo-Burrows (Communicare)
Business organisations are increasingly viewing knowledge as their most valuable and strategic resource to remain competitive. Every organisation has both explicit knowledge, referring to carefully analysed and defined knowledge, and tacit knowledge, referring to complex knowledge, difficult to specify and often unrecorded. Tacit knowledge becomes embedded in an individual's personal expertise and cannot be expressed through the normal use of words. But it is precisely the tacit knowledge that often delivers a sustainable competitive advantage, as it is this part that competitors have difficulty in replicating. Many organisations are realizing that they must explicitly manage their knowledge resources and capabilities, and they have initiated a range of knowledge management programmes. An important managerial responsibility resides in managing the knowledgetransfer context, including the assessment of all knowledge possessed by a firm. This necessitates the conversion of tacit knowledge into explicit knowledge. This article looks at the tacit knowledge literature and focuses on the existing methods of converting tacit knowledge into implicit knowledge in organisations. A pilot survey on existing tacit knowledge articulation in a large South African province is discussed. This has pointed towards a more comprehensive research project, with the aim of providing a model for tacit knowledge communication strategies in South African multicultural firms.